Presence and property: Gendered perspectives on participation in a dairy development program in Kenya and Uganda. (May 2019) - Basu, Pratyusha; Galiè, Alessandra; Baltenweck, Isabelle
Abstract: As women's participation has become central to the formulation and implementation of development programs, gender relations within households and gendered discourses in development programs have been subject to much scrutiny. This paper seeks to expand these notions of gender and development by situating women's participation at the intersections of households and development programs. More specifically, this paper approaches participation as an amalgam of presence and property – the former denoting myriad forms of women's work and knowledge, and the latter denoting access to and control over resources. The case study utilized here is the East Africa Dairy Development (EADD) program which aims to organize small-scale dairy farmers through centralized hubs which improve access to dairy inputs and markets. Based on interviews conducted with women and men in Kenya and Uganda, this paper shows how initiatives that include women construct new pathways for women's participation because of the ways that various participatory strategies relate to one another, rather than due to the efficacy of one strategy over another. Overall, this paper seeks to contribute to gender and development studies by attending to how participation actually emerges in specific contexts through gendered negotiations with participatory development policies. Highlights: Participation is an amalgam of presence (women's work and knowledge) and property (access to and control over resources). Participation is shaped by how various strategies relate to one another, rather than the efficacy of one over another. Women and men use development program's participatory strategies to negotiate gender dynamics within households. Complexities of participation traced through voices of women and men dairy farmers.